PERAN BELANJA PEMERINTAH DAN HUMAN CAPITAL TERHADAP PENGANGURAN DAN KEMISKINAN DI INDONESIA - Shofwatun Hasna (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2016)
This study aims to analyze the performance of government spending and human capital for unemployent and poornes since six year (2010-2015). The panel model chosen is random effect, the analysis result shows that (1) The unemployement in the district is lower than in the city, and commodity of food has highest influence for the poorness; (2) The growth of government spending has positive impact to aggrerate output, even it doesn’t optimal yet, The case is the allocation for government spending is low, and the highest allocation is for sipil employment budgets; (3) Using simultant regression, Government spending and Human Development Index (HDI) have no impact to unemployment; but by using partial regression, government spending has positive impact and HDI has negative impact to unemployment; (4) Using simultant regression, government spending has positive impact and HDI has negative impact to poorness. But by using partial regression, both of them have no impact to poorness.